Iodine-mediated hydration of alkynes on keto-functionalized scaffolds: mechanistic insight and the regiospecific hydration of internal alkynes - Lee, Zachary; Jones, Brandon R.; Nkengbeza, Nyochembeng; Phillips, Michael; Valentine, Kayla; Stewart, Alexis; Sellers, Brandon; Shuber, Nicholas; Aiken, Karelle S. (Beilstein Journal of Organic Chemistry, 2019)
An iodine-mediated hydration reaction of alkynes serves as a green alternative to metal-catalyzed procedures. Previous work has shown that this method works well with terminal alkynes on keto-functionalized scaffolds, including 1,3-dicarbonyls and their heteroatom analogues. It was hypothesized that the reaction proceeds through a 5-exo-dig neighboring group participation (NGP) cyclization and an α-iodo intermediate. The work described herein probes the existence of the intermediate through NMR investigations and explores the scope of the hydration process with internal alkynes. The NMR experiments confirm the existence of the α-iodo intermediate, and methodology studies demonstrate that alkyl-capped, asymmetric, internal alkynes undergo a regiospecific hydration, also via the 5-exo-dig NGP pathway.
Keywords: α-iodo intermediate; internal alkyne; iodine-mediated hydration; neighboring group participation; regiospecific hydration